Does Dexmedetomidine Improve or Worsen Restless Leg Syndrome under Sedation: A Case Report and Extensive Review - Sandra Iskandar; Marina Souto Martins; Andrew Hudson; Jason G. Hirsch; Jonathan S. Jahr (Case Reports in Critical Care, 2022)
Background. Restless leg syndrome (RLS) is a common neurological condition that manifests as creeping, nonpainful urges to move lower extremities and is relieved with movements of the legs. RLS is associated with comorbidities such as gastric surgery, diabetes mellitus, uremia, and iron deficiency anemia, and it is misdiagnosed in many cases. Drugs like levodopa, ropinirole, pramipexole, cabergoline, and pergolide that target the dopaminergic system have been traditionally used to treat symptoms of RLS. α2-adrenoceptor (α2-AR) agonists, like clonidine and dexmedetomidine, have also been reported to show improvement of RLS symptoms during sedation. Specific Aim. This case report suggests that dexmedetomidine may have worsened RLS during sedation in a 71-year-old male with no prior diagnosis of RLS or reported symptoms. The patient had a procedure for right first metatarsophalangeal joint (MTPJ) fusion, with second digit proximal interphalangeal joint (PIPJ) arthrodesis, and flexor tendon transfer due to pain on walking and failing conservative therapy. He underwent intravenous sedation/monitored anesthesia care (MAC) with propofol, dexmedetomidine, and a peripheral regional block for intraoperative anesthesia and postoperative analgesia. During the surgery, the patient experienced continuous bilateral leg movement, unpredictable, and unrelated to surgical stimulation or level of consciousness within 5 minutes of administration of dexmedetomidine. The patient tolerated the procedure, and the unpredicted leg movement was managed by the surgeons intraoperatively. Conclusion. Although no previous literature exists and mechanisms are unclear, this case report hypothesizes that dexmedetomidine may contribute to worsening RLS symptoms.